Perception of disaster preparedness and participation in training are associated with disaster preparedness among health workers - I Made Dwie Pradnya Susila; Pande Putu Januraga; Ni Wayan Arya Utami (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: Disaster preparedness is crucial for health workers in order to provide relief to communities affected by disasters quickly and precisely. However currently there are only few health workers who are prepared to face disasters. This study aims to determine the association between knowledge in disaster management, perception of disaster preparedness, participation in training and experience in disaster management with disaster preparedness in health workers. Methods: A cross sectional survey was conducted among health workers at Petang and Abiansemal public health centres (PHCs). Of the six PHCs in Petang and Abiansemal Sub-districts, four were randomly selected consisting of one PHC in Petang Sub-district and three PHCs in Abiansemal Sub-district. All health workers (271 people) in the four PHCs were selected as respondents. Individual face-to-face interviews were conducted by the first author during April 2018 in the workplaces of each respondent using a pre-tested questionnaire. Data collected consisted of socio-demographic characteristics, knowledge in disaster management, perceptions of disaster preparedness, participation in training, experiences in disaster management and disaster preparedness. Questions consisted of three components namely knowledge in disaster management (12 items), perception of disaster preparedness (32 items) and disaster preparedness (25 items). Bivariate analysis was conducted with chi square test and multivariate analysis with binary logistic regression to determine the association between knowledge, perception, participation in training and experience in disaster management with disaster preparedness. Results: The results showed that 70.9% of respondents had attended disaster training, 40.6% had good knowledge, 24.7% had participated in disaster management and 49.1% had a high level of disaster preparedness. The variables significantly associated with disaster preparedness were perceptions of disaster preparedness (AOR=6.40; 95%CI: 3.71-10.99) and participation in disaster training (AOR=2.68; 95%CI: 1.44-4.97). Conclusion: Disaster preparedness among PHC health workers remains low. Perception of disaster preparedness and participation in training are significantly associated with disaster preparedness. Continuous training is needed to increase disaster preparedness among health workers.